THE HISTORICAL MANUSCRIPTS COMMISSION: AN ARCHIVAL EVOLUTION. Issue 2 (1st October 2020) - Gale, Philip; Lomas, Elizabeth
Abstract : The creation of the Royal Historical Manuscripts Commission formed part of a wider movement of institutional renewal and reform in mid-Victorian Britain, including growing professionalisation of both public administration and the academic study of history, particularly from the 1850s. Two features of the commission's work continued to influence its development and The National Archives' engagement with the archives sector today: first, the need to respect the legitimate rights and interests of both individuals and organisations, and second, the relationships by necessity based on collaboration with many partners. This has led to the evolution of a distinctive British mixed economy embracing public and private archives. This article considers the Commission's evolution from surveying and publishing reports on the contents and locations of private collections to becoming the central advisory body on all issues related to archives and manuscripts not covered by the 1958 Public Records Act. The social and technological changes over this time have had a profound influence on the commission's professional practices. In addition, the range and rights of stakeholders have evolved, presenting new challenges. Meeting all the demands and possibilities of the commission's delivery needs to be seen in the context of frequently operating with significant resource constraints.